\(a, b, c\) ক্রমিক সমানুপাতী হলে প্রমান করো যে, \(\cfrac{1}{b^2}=\cfrac{1}{b^2-a^2}+\cfrac{1}{b^2-c^2}\) Madhyamik 2007


\(a, b, c\) ক্রমিক সমানুপাতী হলে \(\cfrac{a}{b}=\cfrac{b}{c}\)
ধরি, \(\cfrac{a}{b}=\cfrac{b}{c}=k [k\ne 0]\)
\(\therefore a=bk=ck^2,\) এবং \(b=ck\)

বামপক্ষ=\(\cfrac{1}{b^2}\)
\(=\cfrac{1}{(ck)^2}\)
\(=\cfrac{1}{c^2k^2}\)

ডানপক্ষ \(=\cfrac{1}{b^2-a^2}+\cfrac{1}{b^2-c^2}\)
\(=\cfrac{1}{(ck)^2-(ck^2)^2}+\cfrac{1}{(ck)^2-c^2}\)
\(=\cfrac{1}{c^2k^2-c^2k^4}+\cfrac{1}{c^2k^2-c^2}\)
\(=\cfrac{1}{c^2k^2(1-k^2)}+\cfrac{1}{c^2(k^2-1)}\)
\(=\cfrac{1}{c^2k^2(1-k^2)}-\cfrac{1}{c^2(1-k^2)}\)
\(=\cfrac{1-k^2}{c^2k^2(1-k^2)}\)
\(=\cfrac{1}{c^2k^2}\)

\(\therefore\) বামপক্ষ = ডানপক্ষ (প্রমাণিত)

Similar Questions